도심환경 군사작전을 위한 DOP 기반의 UAV 지원 측위 기법 - 박민지; 임재성; 백호기 (국방품질연구논집(JDQS), 2022)
With the advent of the NCW, the modern warfare has undergone various changes, such as local provocation, assassination, and terrorism in urban areas rather than all-out war. At the same time, achieving information superiority and real-time awareness of the situation act as a very important factor in determining the victory or defeat of the battlefield. Most weapon systems are equipped with GPS receivers to acquire location information, which is the core of battlefield information. However, there are moments when GNSS including GPS cannot provide the required level of performance due to environmental characteristics in urban environments and weak satellite signals. It is a very important issue to improve the vulnerability of GNSS in order to achieve information superiority, which is the core of NCW operations. In this paper, we propose a DOP(Dilution of Precision)-based UAV assisted positioning technique that maintains positioning performance in real time to support military operations in urban areas. Through simulation, it was shown that location accuracy was improved and reliable military operation support was possible. Also, based on the proposed technique, a UAV model that can be operated in a real environment is presented.
Keywords: GNSS; Situation awareness; UAV-assisted positioning; Dilution of precision; Location accuracy